Psychometric Evaluation of the Persian Version of Family Collaboration Scale: Collaboration between Relatives of Older Patients and Nurses - Asgari, Nafiseh; Nikpeyma, Nasrin; Haghparast, Atefeh; Yeganeh, Leila Teymouri; Kolagari, Shohreh (Bangladesh Journal of Medical Science, 2025)
Background Family-nurse collaboration is critical when caring for hospitalized elderly patients. In order to assess this collaboration in clinical settings, a scale based on the culture of the local country is required. This study aimed to investigate the Psychometric Evaluation of Persian version of Family Collaboration Scale (FCS). Material and Methods This methodological study measured the FCS in hospitals affiliated with Golestan University of Medical Sciences in 2022. After permission was obtained from the developer, the FCS was translated from English into Persian and back-translated into English based on the World Health Organization’s model. The translated version was then examined for its psychometric properties, including initial reliability, face validity, content validity, construct validity, convergent validity, and overall reliability. Ultimately, the reliability of the Persian version was assessed using the Intraclass Correlation Coefficient (ICC), Cronbach’s alpha, and McDonald’s Omega coefficient. The obtained data were analyzed statistically in SPSS- 16 and AMOS-24. Results The initial reliability of the whole scale and its subscales was confirmed with values greater than 0.7. Regarding qualitative face validity, some items of the scale were modified based on the comments of the target groups. The calculation of the item factor, CVR, and CVI led to the confirmation of 42 items, the elimination of 5 items, and the confirmation of the remaining items, respectively. In addition, 6 items were eliminated following exploratory factor analysis. Finally, there remained a total of 31 items on the scale. The next step was built on a confirmatory factor analysis approach and fit indices, demonstrating that the FCS could be used in the Iranian population. In addition, CR>0.7, AVE>0.5, and CR>AVE confirmed the convergent validity of this scale. Cronbach’s alpha, McDonald Omega coefficient (Ω), and ICC (test-retest) for this scale were obtained as 0.87, > 0.80, and 0.82, respectively. Moreover, there was a significant correlation between the two stages of the test (p<0.001). As a result, the reliability of the Persian version of the FCS was confirmed. Conclusion The translation and psychometric evaluation of the FCS suggested that it is a valid and reliable scale that can be used in Iran to evaluate how well families of elderly patients and nurses collaborate in clinical settings. BJMS, Vol. 24 No. 04 October’25 Page : 1197-1207